Susannah (Brigantine) records - Susannah (Brigantine)
Ship certification and license (1803 February 21) issued to Captain Richard Thornton for the Susannah and customs receipt (1803 July 1) issued at Saint Domingue (later part of the Dominican Republic).
Vessel sailing out of Baltimore, Md., under Captain Richard Thornton, trading with the West Indies.
Collection material in English, with French.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Thornton, Richard, -- Captain; Ship's papers -- 19th century; Baltimore (Md.) -- Commerce -- West Indies; Barbados -- History; Dominican Republic -- History -- To 1844.; West Indies -- Commerce -- Maryland -- Baltimore